An Analysis of the Features of Words That Influence Vocabulary Difficulty - Elfrieda H. Hiebert; Judith A. Scott; Ruben Castaneda; Alexandra Spichtig (MDPI AG, 2019)
The two studies reported on in this paper examine the features of words that distinguish students’ performances on vocabulary assessments as a means of understanding what contributes to the ease or difficulty of vocabulary knowledge. The two studies differ in the type of assessment, the types of words that were studied, and the grade levels and population considered. In the first study, an assessment of words that can be expected to appear with at least moderate frequency at particular levels of text was administered to students in grades 2 through 12. The second study considered the responses of fourth- and fifth-grade students, including English learners, to words that teachers had identified as challenging for those grade levels. The effects of the same set of word features on students’ vocabulary knowledge were examined in both studies: predicted appearances of a word and its immediate morphological family members, number of letters and syllables, dispersion across content areas, polysemy, part of speech, age of acquisition, and concreteness. The data consisted of the proportion of students who answered an item correctly. In the first study, frequency of a word’s appearance in written English and age of acquisition predicted students’ performances. In the second study, age of acquisition was again critical but so too were word length, number of syllables, and concreteness. Word location (which was confounded by word frequency) also proved to be a predictor of performance. Findings are discussed in relation to how they can inform curriculum, instruction, and research.